Design rainfall temporal patterns for upper Klang catchment - Hong, Jer Lang; Md Jafri, Azmi; Ibrahim, Izihan; Shafie, Suzana; Hong, Kee An; Naubi, Irena (The Institution of Engineers, Malaysia, 2018)
Rainfall temporal patterns are needed as inputs for hydrologic models such as unit hydrograph or runoff routing method used in the derivation of flood hydrographs. The patterns adopted can have a major effect on the resulting flood computed. Short and long duration rainfall data are both required for different sizes of catchments to determine and locate the flood producing critical storms in flood estimation. Design temporal patterns with different durations are therefore also required for distributing the storm rainfall in flood calculations. Patterns for a large number of durations with reasonably short time intervals are needed by designers to reduce the need for interpolation and to maintain the accuracy in obtaining the peak of the hydrograph. In this study, pluviograph data for the Upper Klang Catchment with records of over 30 years are used to derive temporal patterns for 20 standard durations as per ARR87. Rainfall temporal patterns for the upper Klang were derived for rainfall durations from 10 minutes to 72 hours and for time intervals from 5 minutes to 4 hours. The patterns presented in this study demonstrate the use of Average Variability Method in deriving design rainfall temporal patterns for data of the Klang Catchment and the patterns derived can be used for design flood estimations for catchments in the same general region.